2019
DOI: 10.5194/nhess-19-2781-2019
|View full text |Cite
|
Sign up to set email alerts
|

Post-event field survey of 28 September 2018 Sulawesi earthquake and tsunami

Abstract: Abstract. An earthquake with a magnitude of Mw=7.5 that occurred in Sulawesi, Indonesia, on 28 September 2018 triggered liquefaction and tsunamis that caused severe damage and many casualties. This paper reports the results of a post-tsunami field survey conducted by a team with members from Indonesia and Taiwan that began 13 d after the earthquake. The main purpose of this survey was to measure the run-up of tsunami waves and inundation and observe the damage caused by the tsunami. Measurements were made in 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 17 publications
0
31
0
2
Order By: Relevance
“…Run-up heights (Omira et al 2019;Widiyanto et al 2019) and flow depths (Pribadi et al 2018;Muhari et al 2018) were observed during field surveys (Fig. 1a).…”
Section: Field Survey Datamentioning
confidence: 81%
See 2 more Smart Citations
“…Run-up heights (Omira et al 2019;Widiyanto et al 2019) and flow depths (Pribadi et al 2018;Muhari et al 2018) were observed during field surveys (Fig. 1a).…”
Section: Field Survey Datamentioning
confidence: 81%
“…It is difficult to know whether the flow depth data includes splash heights. Therefore, we compared our calculated run-up heights with run-up heights (Omira et al 2019;Widiyanto et al 2019) alone. We used run-up heights including the tidal elevation at the time of the earthquake from the reports.…”
Section: Field Survey Datamentioning
confidence: 99%
See 1 more Smart Citation
“…It is famous for the 1883 Krakatau eruption, which caused a 30 m tsunami that led to 36 000 fatalities and affected Earth's climate and weather for several weeks, as reported by Verbeek (1884). The 1883 eruption of Krakatau and the resulting tsunami have been widely discussed (e.g., Yokoyama, 1987;Camus et al, 1992;Maeno and Imamura, 2011;Paris et al, 2014). A young volcano called Anak Krakatau (Child of Krakatau) appeared above sea level in 1929.…”
Section: Introductionmentioning
confidence: 99%
“…Also, tsunamis may be regarded as low frequency events but with high impacts in terms of human/infrastructure/economic losses. Their power of destruction has been more than evident in recent years [2][3][4][5][6][7][8][9][10][11]. It is believed that from the time period between 1998 and 2017, the losses inflicted by tsunami disasters were a total of US$280 billion and 251,770 causalities, in damages [7].…”
Section: Introductionmentioning
confidence: 99%